Interactions of Aspergillus fumigatus Conidia with Airway Epithelial Cells: A Critical Review - Croft, Carys A.; Culibrk, Luka; Moore, Margo M.; Tebbutt, Scott J. (Frontiers in Microbiology, 2016)
Aspergillus fumigatus is an environmental filamentous fungus which also acts as an opportunistic pathogen able to cause a variety of symptoms, from an allergic response to a life-threatening disseminated fungal infection. The infectious agents are inhaled conidia whose first point of contact is most likely to be an airway epithelial cell. The interaction between epithelial cells and conidia is multifaceted and complex, and has implications for later steps in pathogenesis. Increasing evidence has demonstrated a key role for the airway epithelium in the response to respiratory pathogens, particularly at early stages of infection; therefore, elucidating the early stages of interaction of conidia with airway epithelial cells is essential to understand the establishment of infection in cohorts of at-risk patients. Here, we present a comprehensive review of the early interactions between A. fumigatus and airway epithelial cells, including bronchial and alveolar epithelial cells. We describe mechanisms of adhesion, internalization of conidia by airway epithelial cells, the immune response of airway epithelial cells, as well as the role of fungal virulence factors and patterns of fungal gene expression characteristic of early infection. A clear understanding of the mechanisms involved in the early establishment of infection by A. fumigatus could point to novel targets for therapy and prophylaxis.